Synthesis and photoluminescence behavior of Bi4Ti3O12 powders obtained by the complex polymerization method - Oliveira, R. C.; Cavalcante, L. S.; Sczancoski, J. C.; Aguiar, E. C. [UNESP]; Espinosa, J. W. M. [UNESP]; Varela, José Arana [UNESP]; Pizani, P. S.; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2009)
Bismuth titanate, Bi4Ti3O12(BiT) powders were synthesized by the complex polymerization method. The structural evolution as a function of heat treatment temperature of these powders was analyzed by X-ray diffraction (XRD) and micro-Raman (MR) spectroscopy. The optical properties were verified by ultraviolet-visible (UV-vis) absorption spectroscopy and photoluminescence (PL) measurements. XRD patterns and MR spectra revealed that the BiT powders heat treated at 700 degrees C for 2 h under oxygen flow crystallize in an orthorhombic structure without deleterious phases. UV-vis spectra indicated the presence of intermediary energy levels within the band gap of the powders heat treated at low temperatures. The maximum PL emissions of these materials were verified at around 598 nm, when excited by 488 nm wavelengths. Also, it was observed the presence of two broad PL bands, which were attributed to the intermediary energy levels arising from alpha-Bi2O3 and BiT phases. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Clusters; Chemical synthesis; Optical properties; Luminescence